Analysis of Risk Management Cycle on Capitation Mechanism at First Level Healthcare Facilities in East Java - Rachmad Suhanda; Usman Hadi; Widodo J. Pudjirahardjo; Djazuly Chalidyanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
The implementation of risk management is an essential function in an organization to control risk. Basedon the preliminary research that has been carried out, only 4.2% of FLHF in East Java implemented thecomplete risk management process, starting from establishing context to evaluating risks. Modificationsof risk management cycle implementation are made by reviewing the opinion of Carroll (2001) and ISO31000:2009. This research aims to analyze the influence between the stages of implementing modified riskmanagement based at 95 FLHF in East Java. The results show that each stage of the capitation mechanismrisk management has a strong significant influence on each other. The results provide recommendation thatFLHF should improve the understanding and awareness of the risks and expected to be able to apply riskmanagement cycle as a whole.